A method for preparing carbon quantum dots from biomass waste

Through the methods of pyrolysis of fir and nitric acid oxidation and cutting, the problem of using expensive materials and polluting the environment in the existing carbon quantum dot preparation methods is solved, and efficient and stable carbon quantum dots are economically and environmentally friendly to prepare efficient and stable carbon quantum dots from biomass waste.

CN116177532BActive Publication Date: 2025-04-29NANJING AGRICULTURAL UNIVERSITY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310049425.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-01
Publication Date
2025-04-29
Estimated Expiration
2043-02-01

AI Technical Summary

Technical Problem

The existing carbon quantum dot preparation methods use expensive materials, and the preparation process is prone to pollute the environment.

Method used

Biochar was prepared by pretreating fir as a precursor material, pyrolyzing, and carbon quantum dots were extracted by nitric acid oxidation cleavage, and finally purification, separation and characterization were performed.

Benefits of technology

The production of carbon quantum dots from biomass waste is achieved economically and environmentally friendly, reducing the preparation cost, and the produced products have good fluorescence performance and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116177532B_ABST
    Figure CN116177532B_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing carbon quantum dots from waste biomass, belonging to the field of nanomaterial preparation. Biochar is prepared by pyrolyzing the precursor material Chinese fir after pretreatment under oxygen-limited conditions, and then the biochar is ground and sorted, added to nitric acid with a concentration of 6 mol·L-1 at 110 °C, and an oxidation cutting reaction is carried out. After the reaction, the pH of the product is adjusted, and then centrifuged and dialyzed to obtain carbon quantum dots. Finally, the product is ultrafiltered and separated to purify and obtain finished products with different particle sizes. The present invention uses common waste biomass to prepare carbon quantum dots, which has the advantages of environmental protection, realizes the recycling and reuse of biomass resources, overcomes the disadvantages of high cost and narrow material sources in the previous methods for preparing carbon quantum dots, and opens up a new idea for the preparation of carbon quantum dots.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nano material preparation, and in particular to a method for preparing carbon quantum dots from biomass waste. Background Art

[0002] Carbon quantum dots (CQDs) refer to carbon nanomaterials with a particle size of less than 10nm and special properties (such as fluorescence). As a new type of nanomaterial, CQDs are increasingly used in the environment, biology, medicine, etc., and their preparation methods are also attracting more and more attention.

[0003] At present, there are two main methods for preparing CQDs: Top-down and Bottom-up. Top-down refers to cutting large carbon materials into nanoparticles under external effects such as arc and oxidation, mainly including arc discharge method, electrochemical oxidation method, etc. Bottom-up is just the opposite, and is prepared by synthesizing and aggregating organic molecules, mainly including hydrothermal method and microwave method.

[0004] Although the above two methods are the most commonly used methods for preparing CQDs, the materials used in this method are relatively expensive, such as graphene and carbon fiber, and are prone to environmental pollution during the preparation process. Biochar, as a carbon-rich material, is generally obtained by pyrolysis of biomass. For example, the biochar yield of rice straw is 26.43%, and the biochar yield of corn straw is 28.75%. It is an economical, environmentally friendly, cheap and easily available material.

[0005] Therefore, there is an urgent need for an environmentally friendly and economical method for preparing carbon quantum dots by pyrolyzing waste biomass and further oxidizing the products. Summary of the invention

[0006] The technical problem solved by the present invention is that the materials used in the existing carbon quantum dot preparation method are relatively expensive and are likely to cause environmental pollution during the preparation process.

[0007] To solve the above problems, the technical solution of the present invention is as follows:

[0008] A method for preparing carbon quantum dots from biomass waste comprises the following steps:

[0009] S1. Using Chinese fir as a precursor material and pretreating the precursor material;

[0010] S2, preparing a biochar sample by pyrolysis of the pretreated precursor material;

[0011] S3, oxidative cutting of the biochar sample by nitric acid to extract carbon quantum dots;

[0012] S4. Purify, separate and characterize the carbon quantum dots.

[0013] Furthermore, the pretreatment is as follows: the fir is washed with deionized water for 3 to 5 times and then dried, then the fir is crushed, and finally passed through a 100-mesh sieve with a pore size of 0.154 mm, and then packed in a brown bottle for standby use.

[0014] Note: Compared with other materials such as straw, fir wood biomass has fewer impurities, is easier to process, and has a higher purity. Therefore, fir with a wide source and large output is randomly selected as the raw material.

[0015] Further, the drying operation comprises the following steps:

[0016] S1-1, cutting the fir into the same length, placing the cut fir in a wood drying kiln, heating the wood drying kiln at a rate of 4-5°C per hour until it reaches 70°C, keeping the temperature for 2 hours, and then naturally cooling the wood drying kiln to 55°C;

[0017] S1-2, heating the wood drying kiln at a rate of 9-10°C / h to 60°C, keeping it warm for 2 hours, then heating it up to 75°C at a rate of 4°C per hour, keeping it warm for 2 hours;

[0018] S1-3. Raise the temperature of the wood drying kiln at a rate of 4°C / h to 85°C and keep it warm for 4h.

[0019] Note: Drying operation can improve the utilization rate of fir.

[0020] Furthermore, the same length ranges from 5 to 10 cm.

[0021] Note: The shorter length of fir can shorten the drying time.

[0022] Further, step S2 includes the following steps:

[0023] S2-1, weigh 100 g of the pretreated precursor material into a crucible, compact it and cover the crucible with a lid, seal it in an atmosphere furnace and turn on a vacuum pump to evacuate the air;

[0024] S2-2. When the pressure in the atmosphere furnace drops to -30 kPa, turn on the nitrogen pump to fill nitrogen to raise the pressure in the furnace to 30 kPa, then turn on the vacuum pump to exhaust, repeat this cycle three times, and finally set the nitrogen flow rate to 2 L min -1 and at 5℃·min -1 Increase the furnace temperature to 900℃ at a rate of , and maintain it for 2h;

[0025] S2-3. After the pyrolysis is completed, the atmosphere furnace is cooled to room temperature, the cooled biochar is weighed, the yield of the biochar is calculated and ground into 100 meshes to obtain a biochar sample.

[0026] Note: Biochar is used here because: the same operation was performed on activated carbon, and it was found that the yield of carbon quantum dots produced by coal-based activated carbon was very low and the effect was very poor; and biochar can be produced from agricultural and forestry waste, and its cost is lower than that of activated carbon.

[0027] Further, step S3 includes the following steps:

[0028] S3-1. Place 2 g of biochar sample in a condensation reflux device containing nitric acid and heat it to 100-120°C. The concentration of nitric acid is 4-6 mol / L and the volume is 150 mL. Turn on the condensation water to reflux for 12-20 hours at a reflux temperature of 100-120°C. Allow the suspension to cool naturally to room temperature.

[0029] S3-2. Take out the suspension, adjust the pH of the suspension to 7.0 with sodium carbonate powder and 5% sodium bicarbonate solution, centrifuge at 8000 g for 10 min, and collect the supernatant as carbon quantum dots.

[0030] Note: Nitric acid is used here instead of sulfuric acid because sulfuric acid has a stronger oxidizing ability, which will lead to a decrease in yield.

[0031] Further, step S4 includes the following steps:

[0032] S4-1, pre-treating a dialysis bag with a pore size of 200Da, placing the carbon quantum dots in the pre-treated dialysis bag, and dialyzing the dialysis bag in deionized water for one week to remove inorganic salts in the carbon quantum dots;

[0033] S4-2. Under the action of centrifugation at 10000g for 10 min, the carbon quantum dots were separated by ultrafiltration through MWCO membranes with pore sizes of 3 kDa and 10 kDa, and finally carbon quantum dots with particle sizes of less than 3 kDa, 3 to 10 Da, and greater than 10 kDa were obtained.

[0034] Note: The molecular weight cut-off of 200Da ensures good performance of the product to a certain extent, and the product in the membrane is well separated from the impurities to be removed.

[0035] Furthermore, the pretreatment includes: cutting a dialysis bag with a pore size of 200Da into an appropriate length, boiling it in deionized water for 5 to 10 minutes, and then washing it with distilled water to remove trace amounts of sulfides, heavy metals and some ultraviolet absorbing impurities on the surface.

[0036] Furthermore, step S4 further includes:

[0037] S4-3. The total organic carbon content of the carbon quantum dots was determined by a total organic carbon analyzer, and the carbon quantum dots were characterized by atomic force microscopy, X-ray photoelectron spectroscopy, and fluorescence spectrophotometer.

[0038] The beneficial effects of the present invention are:

[0039] (1) The present invention uses low-cost and easily available biomass waste to prepare widely used carbon quantum dots, which is expected to reduce the preparation cost of carbon quantum dots, break through the preparation and promotion and application barriers of carbon quantum dots, and achieve the purpose of economical, efficient and safe preparation of carbon quantum dots;

[0040] (2) The present invention utilizes biomass waste to prepare carbon quantum dots, which not only has an easy-to-obtain carbon source and a high yield, but also has a low cost and is green and environmentally friendly. The obtained product has good water solubility, high stability, and good fluorescence properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 is a structural diagram of the condensation reflux device in Example 1;

[0042] Figure 2 1 is an analysis diagram of the effect of different reflux temperatures on the prepared products in Example 1, Example 2 and Example 3;

[0043] Figure 3 1. It is an analysis diagram of the effect of different reflux times on the prepared products in Example 4, Example 5 and Example 6;

[0044] Figure 4 7 and 8 are analysis diagrams showing the effects of different nitric acid concentrations on the prepared products;

[0045] Figure 5 is an atomic force microscopy image of carbon quantum dots with a molecular weight less than 3 kDa in Example 9;

[0046] Figure 6 is an atomic force microscopy image of carbon quantum dots with a molecular weight greater than 10 kDa in Example 9;

[0047] Figure 7 is an atomic force microscopy image of carbon quantum dots with a molecular weight between 3 kDa and 10 kDa in Example 9;

[0048] Figure 8 is a fluorescence spectrum of the carbon quantum dots prepared in Example 10 at different excitation wavelengths;

[0049] Fig. 9 is the fluorescence spectra of the carbon quantum dots prepared in Example 3 at different excitation wavelengths;

[0050] Fig.10This is a characterization diagram of the X-ray photoelectron spectroscopy results of the carbon quantum dots prepared in Example 10;

[0051] Fig.11 The present invention is a flow chart of a method for preparing carbon quantum dots from biomass waste. DETAILED DESCRIPTION

[0052] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0053] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms "a", "said" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings, and "multiple" generally includes at least two.

[0054] It should be understood that although the terms first, second, third, etc. may be used to describe ... in the embodiments of the present invention, these ... should not be limited to these terms. These terms are only used to distinguish .... For example, without departing from the scope of the embodiments of the present invention, the first ... may also be referred to as the second ..., and similarly, the second ... may also be referred to as the first ....

[0055] Example 1

[0056] This embodiment is a method for preparing carbon quantum dots from biomass waste. Fig.11 As shown, the following steps are included:

[0057] S1. Using Chinese fir as a precursor material, the precursor material is pretreated. The pretreatment is as follows: washing the Chinese fir with deionized water for 3 times and then drying it, then crushing the Chinese fir, and finally passing it through a 100-mesh sieve with a pore size of 0.154 mm, and putting it in a brown bottle for standby use. The drying operation includes the following steps:

[0058] S1-1, cutting the fir into the same length of 5 cm, and then placing the cut fir into a wood drying kiln, heating the wood drying kiln at a rate of 4°C / h until it reaches 70°C, keeping the temperature for 2h, and then naturally cooling the wood drying kiln to 55°C;

[0059] S1-2, heating the wood drying kiln at a rate of 9°C / h to 60°C, keeping it warm for 2 hours, then heating it at a rate of 4°C per hour to 75°C, keeping it warm for 2 hours;

[0060] S1-3, heating the wood drying kiln at a rate of 4°C / h until it reaches 85°C and keeping the temperature for 4h;

[0061] S2. Preparing a biochar sample by pyrolysis of the pretreated precursor material, comprising the following steps:

[0062] S2-1, weigh 100 g of the pretreated precursor material into a crucible, compact it and cover the crucible with a lid, seal it in an atmosphere furnace and turn on a vacuum pump to evacuate the air;

[0063] S2-2. When the pressure in the atmosphere furnace drops to -30 kPa, turn on the nitrogen pump to fill nitrogen to raise the pressure in the furnace to 30 kPa, then turn on the vacuum pump to exhaust, repeat this cycle three times, and finally set the nitrogen flow rate to 2 L min -1 and at 5℃·min -1 Increase the furnace temperature to 900℃ at a rate of , and maintain it for 2h;

[0064] S2-3, after the pyrolysis is completed, the atmosphere furnace is cooled to room temperature, the cooled biochar is weighed, the yield of the biochar is calculated and ground into 100 meshes to obtain a biochar sample;

[0065] S3, oxidative cutting of the biochar sample by nitric acid to extract carbon quantum dots, comprising the following steps:

[0066] S3-1. Place 2 g of biochar sample in a condensation reflux device containing nitric acid and heat to 100°C. The concentration of nitric acid is 6 mol / L and the volume is 150 mL. Turn on the condensation water and reflux for 20 hours. The reflux temperature is 100°C. Wait for the suspension to cool naturally to room temperature.

[0067] S3-2, taking out the suspension, adjusting the pH of the suspension to 7.0 with sodium carbonate powder and 5% sodium bicarbonate solution, and centrifuging at 8000g for 10 min, collecting the supernatant as carbon quantum dots;

[0068] S4, purifying, separating and characterizing the carbon quantum dots, comprising the following steps:

[0069] S4-1, pre-treating a dialysis bag with a pore size of 200Da, placing the carbon quantum dots in the pre-treated dialysis bag, and dialyzing the dialysis bag in deionized water for one week to remove inorganic salts in the carbon quantum dots;

[0070] S4-2, under the action of centrifugation at 10000g for 10 minutes, the carbon quantum dots were separated by ultrafiltration through MWCO membranes with pore sizes of 3kDa and 10kDa, and finally carbon quantum dots with particle sizes of less than 3kDa, 3-10Da and greater than 10kDa were obtained. The pretreatment included: cutting a dialysis bag with a pore size of 200Da into appropriate lengths, boiling it in deionized water for 5-10 minutes, and then washing it with distilled water to remove trace amounts of sulfides, heavy metals and some ultraviolet absorbing impurities on the surface;

[0071] S4-3. The total organic carbon content of the carbon quantum dots was determined by a total organic carbon analyzer, and the carbon quantum dots were characterized by atomic force microscopy, X-ray photoelectron spectroscopy, and fluorescence spectrophotometer.

[0072] In this embodiment, the condensation reflux device is as follows Figure 1 shown.

[0073] In step S4-3 of this embodiment, the prepared carbon quantum dots are diluted 100 times with water and then placed in a centrifuge tube and marked. The water sample is then placed in a total organic carbon analyzer to determine the total organic carbon content, and finally the data is analyzed.

[0074] Example 2

[0075] This embodiment is a method for preparing carbon quantum dots from biomass waste, which is different from Embodiment 1 in that:

[0076] In step S3-1, the reflux temperature is 110°C.

[0077] Example 3

[0078] This embodiment is a method for preparing carbon quantum dots from biomass waste, which is different from Embodiment 1 in that:

[0079] In step S3-1, the reflux temperature is 120°C.

[0080] In step S4-3 of this embodiment, the fluorescence properties of the prepared CQDs are analyzed using a F97Pro fluorescence spectrophotometer. CQDs are added to about two-thirds of the quartz cuvette for fluorescence testing. The fluorescence values ​​at the emission wavelength of 300-700nm are detected when the excitation wavelength is 370, 390, 400, 420, 440, 450, 460, 470, 480, and 500nm, respectively. Fig. 9 As shown in the figure, the prepared CQDs show typical excitation wavelength dependence characteristics. As the excitation wavelength increases from 370nm to 500nm, the fluorescence intensity of CQDs increases first and then decreases, and the emission peak position also changes.

[0081] The preparation conditions of carbon quantum dots in Example 1, Example 2 and Example 3 are shown in Table 1. As can be seen from Table 1, the difference between the preparation conditions of Example 1, Example 2 and Example 3 is the different reflux temperatures. The products were observed and the total organic carbon content was measured using a total organic carbon analyzer. The results are as follows: Figure 2 As shown, the results show that 110℃ is the optimal reflux temperature.

[0082] Table 1 Preparation conditions of carbon quantum dots in Example 1, Example 2 and Example 3

[0083] <![CDATA[HNO3 concentration]]> Reflow temperature Reflow time Example 1 6mol / L 100℃ 20h Example 2 6mol / L 110℃ 20h Example 3 6mol / L 120℃ 20h

[0084] Example 4

[0085] This embodiment is a method for preparing carbon quantum dots from biomass waste, which is different from Embodiment 1 in that:

[0086] In step S1, the fir wood is rinsed with deionized water for 4 times.

[0087] In step S1-1, the temperature of the wood drying kiln is increased at a rate of 4.5°C / h.

[0088] In step S1-2, the temperature of the wood drying kiln is increased at a temperature increase rate of 9.5°C / h.

[0089] In step S3-1, the nitric acid concentration is 6 mol / L, the reflux temperature is 110°C, and the reflux time is 12 h.

[0090] Example 5

[0091] This embodiment is a method for preparing carbon quantum dots from biomass waste, which is different from Example 4 in that:

[0092] In step S3-1, the reflux time is 16 h.

[0093] Example 6

[0094] This embodiment is a method for preparing carbon quantum dots from biomass waste, which is different from Example 4 in that:

[0095] In step S3-1, the reflux time is 20 hours.

[0096] The preparation conditions of carbon quantum dots in Example 4, Example 5 and Example 6 are shown in Table 2. As can be seen from Table 2, the difference between the preparation conditions of Example 4, Example 5 and Example 6 is the different reflux time. The products were observed and the total organic carbon content was measured using a total organic carbon analyzer. The results are as follows: Figure 3 As shown, the results show that 20h is the optimal reflux time.

[0097] Table 2 Preparation conditions of carbon quantum dots in Example 4, Example 5 and Example 6

[0098] <![CDATA[HNO3 concentration]]> Reflow temperature Reflow time Example 4 6mol / L 110℃ 12h Example 5 6mol / L 110℃ 16h Example 6 6mol / L 110℃ 20h

[0099] Example 7

[0100] This embodiment is a method for preparing carbon quantum dots from biomass waste, which is different from Example 6 in that:

[0101] In step S1, the fir wood is rinsed with deionized water for 5 times.

[0102] In step S1-1, the wood drying kiln is heated at a rate of 5°C / h.

[0103] In step S1-2, the wood drying kiln is heated at a heating rate of 10°C / h.

[0104] In step S3-1, the concentration of nitric acid is 4 mol / L.

[0105] Example 8

[0106] This embodiment is a method for preparing carbon quantum dots from biomass waste, which is different from Example 7 in that:

[0107] In step S3-1, the concentration of nitric acid is 6 mol / L.

[0108] Table 3 Preparation conditions of carbon quantum dots in Example 7 and Example 8

[0109] <![CDATA[HNO3 concentration]]> Reflow temperature Reflow time Example 7 4mol / L 110℃ 20h Example 8 6mol / L 110℃ 20h

[0110] The preparation conditions of carbon quantum dots in Example 7 and Example 8 are shown in Table 3. As can be seen from Table 3, the difference between the preparation conditions of Example 7 and Example 8 is the different nitric acid concentrations. The products were observed and the total organic carbon content was measured using a total organic carbon analyzer. The results are as follows: Figure 4 As shown, the results show that the optimal nitric acid concentration is 6 mol / L.

[0111] Example 9

[0112] This embodiment is a method for preparing carbon quantum dots from biomass waste, which is different from Embodiment 1 in that:

[0113] In step S4-3 of this embodiment, an atomic force microscope is used to observe the morphology and particle size of CQDs of different particle sizes: a portion of the sample is dispersed in an aqueous solution for ultrasonication, and then a few drops of the dispersed liquid are dripped onto a mica sheet, and after drying, the sample is photographed using a Bruker Dimension Icon AFM instrument with a scanning range of 500 μm × 500 μm. The formed 3D image and plane distribution map are observed.

[0114] In step S4-3 of this embodiment, in the prepared product with a molecular weight of <3 kDa, CQDs are densely and evenly distributed on the observed sample, the largest particle size is 4.5 nm, a small part of the particle size is between 4.5-2.3 nm, and most of the particle size is about 2.0 nm. The horizontal distance is 0.50 μm, the vertical distance is 360.71 μm, the surface distance is 0.50 μm, and the average roughness is 350.42 μm. Figure 5 shown.

[0115] In step S4-3 of this embodiment, in the prepared product with a molecular weight > 10 kDa, CQDs are densely and evenly distributed on the observed sample, most of the particles have a particle size of 10-20 nm, the horizontal distance between particles is 0.5 μm, the vertical distance is -326.80 pm, the surface distance is 0.51 μm, and the average roughness is 1379.06 pm. Figure 6 shown.

[0116] In step S4-3 of this embodiment, in the prepared product with a molecular weight of 3kDa < 10kDa, CQDs are densely and evenly distributed on the observed sample, most of the particles have a particle size of 5-10nm, the horizontal distance between particles is 1.24μm, the vertical distance is -9.00pm, the surface distance is 1.24μm, and the average roughness is 1.36pm. Figure 7 shown.

[0117] Example 10

[0118] This embodiment is a method for preparing carbon quantum dots from biomass waste, which is different from Embodiment 1 in that:

[0119] In step S3-1, the nitric acid concentration is 6 mol / L, the reflux time is 12 h, and the reflux temperature is 110°C.

[0120] In step S4-3 of this embodiment, the fluorescence properties of the prepared CQDs are analyzed using a F97Pro fluorescence spectrophotometer. CQDs are added to about two-thirds of the quartz cuvette for fluorescence testing. The fluorescence values ​​at the emission wavelength of 300-700nm are detected when the excitation wavelength is 370, 390, 400, 420, 440, 450, 460, 470, 480, and 500nm, respectively. Figure 8 As shown in the figure, the prepared CQDs show typical excitation wavelength dependence characteristics. As the excitation wavelength increases from 370nm to 500nm, the fluorescence intensity of CQDs increases first and then decreases, and the emission peak position also changes.

[0121] Embodiment 11

[0122] This embodiment is a method for preparing carbon quantum dots from biomass waste, which is different from Embodiment 1 in that:

[0123] In step S4-3 of this embodiment, the structure of the prepared CQDs was characterized by an Escalab Mark II X-ray spectrometer with a scanning range of 0-1000 eV and a scanning interval of 0.5 eV. In order to analyze the C1 spectral characteristics in detail, a resolution of 0.1 eV was used to scan near 284.6 eV. The measurement results were processed using XPSPeak41, as shown in FIG. Fig.10 As shown. From the figure, we can see that there are different C structures on the surface of CQDs, namely: C=C (284.5eV), CO (286.0eV), and C=O (288.0eV). Among them, the C=C structure on the surface of CQDs accounts for about 85.0%; C=O accounts for about 7.8%; and CO accounts for about 7.2%. The carbonyl and hydroxyl functional groups in C=O and CO are highly active and can mediate electron transfer in the reaction, but their content in the C structure on the surface of CQDs is relatively low, and the combined proportion of the two is only 15.0%.

Claims

1. A method for preparing carbon quantum dots from biomass waste, characterized in that: The following steps are involved: S1. Using Chinese fir as a precursor material and pretreating the precursor material; S2, preparing a biochar sample by pyrolysis of the pretreated precursor material; S3, oxidative cutting of the biochar sample by nitric acid to extract carbon quantum dots; comprising the following steps: S3-1. Place 2 g of biochar sample in a condensation reflux device containing nitric acid and heat it to 100-120°C. The concentration of nitric acid is 4-6 mol / L and the volume is 150 mL. Turn on the condensation water to reflux for 12-20 hours at a reflux temperature of 100-120°C. Allow the suspension to cool naturally to room temperature. S3-2, taking out the suspension, adjusting the pH of the suspension to 7.0 with sodium carbonate powder and 5% sodium bicarbonate solution, and centrifuging at 8000g for 10 min, collecting the supernatant as carbon quantum dots; S4, purifying, separating and characterizing the carbon quantum dots; comprising the following steps: S4-1, pre-treating a dialysis bag with a pore size of 200Da, placing the carbon quantum dots in the pre-treated dialysis bag, and dialyzing the dialysis bag in deionized water for one week to remove inorganic salts in the carbon quantum dots; S4-2. Under the action of centrifugation at 10000g for 10 min, the carbon quantum dots were separated by ultrafiltration through MWCO membranes with pore sizes of 3 kDa and 10 kDa, and finally carbon quantum dots with particle sizes of less than 3 kDa, 3 to 10 Da, and greater than 10 kDa were obtained.

2. A method for preparing carbon quantum dots from biomass waste according to claim 1, characterized in that: The pretreatment is as follows: washing the fir wood with deionized water for 3 to 5 times and then drying the wood, then crushing the wood, and finally passing through a 100-mesh sieve with a pore size of 0.154 mm, and putting the sieve into a brown bottle for standby use.

3. A method for preparing carbon quantum dots from biomass waste according to claim 2, characterized in that: The drying operation comprises the following steps: S1-1, cutting the fir into the same length, placing the cut fir in a wood drying kiln, heating the wood drying kiln at a rate of 4-5°C / h to 70°C, keeping the temperature for 2h, and then naturally cooling the wood drying kiln to 55°C; S1-2, heating the wood drying kiln at a rate of 9-10°C / h to 60°C, keeping it warm for 2 hours, then heating it up to 75°C at a rate of 4°C per hour, keeping it warm for 2 hours; S1-3. Raise the temperature of the wood drying kiln at a rate of 4°C / h to 85°C and keep it warm for 4h.

4. A method for preparing carbon quantum dots from biomass waste according to claim 3, characterized in that: The same length has a value range of 5 to 10 cm.

5. The method for preparing carbon quantum dots from biomass waste according to claim 1, characterized in that: The step S2 comprises the following steps: S2-1, weigh 100 g of the pretreated precursor material into a crucible, compact it and cover the crucible with a lid, seal it in an atmosphere furnace and turn on a vacuum pump to evacuate the air; S2-2. When the pressure in the atmosphere furnace drops to -30 kPa, turn on the nitrogen pump to fill nitrogen to raise the pressure in the furnace to 30 kPa, then turn on the vacuum pump to exhaust, repeat this cycle three times, and finally set the nitrogen flow rate to 2 L min -1 and at 5℃·min -1 Increase the furnace temperature to 900℃ at a rate of , and maintain it for 2h; S2-3. After the pyrolysis is completed, the atmosphere furnace is cooled to room temperature, the cooled biochar is weighed, the yield of the biochar is calculated and ground into 100 meshes to obtain a biochar sample.

6. A method for preparing carbon quantum dots from biomass waste according to claim 1, characterized in that: The pretreatment includes: cutting a dialysis bag with a pore size of 200Da into an appropriate length, boiling it in deionized water for 5 to 10 minutes, and then washing it with distilled water to remove trace amounts of sulfides, heavy metals and some ultraviolet absorbing impurities on the surface.

Citation Information

Patent Citations

  • Method for preparing biomass based carbon quantum dots

    CN104650864A